Double trouble. A cryptic first record of Berghia marinae Carmona, Pola, Gosliner, & Cervera 2014 in the Mediterranean Sea - GALIÀ-CAMPS, CARLES; CARMONA, LEILA; CABRITO, ANDREA; BALLESTEROS, MANUEL (Mediterranean Marine Science, 2020)
In 2014, Berghia marinae Carmona, Pola, Gosliner & Cervera, 2014 from Senegal was described along with the revision of the genus Berghia Trinchese, 1877. In this study, we establish a second record for the senegalese species B. marinae in the Mediterranean Sea, 4,000 Km away from its type location. The morphological mismatch from the original description hampered its identification, and thus, a molecular approach was needed. Multilocus phylogenetic trees were inferred from Maximum-likelihood and Bayesian analyses based on partial DNA sequences of the mitochondrial cytochrome c oxidase subunit I and 16S rRNA genes, and the nuclear gene histone-3. Species delimitation analyses were performed to support the phylogenetic results and a new morphological description is provided complementing earlier information on this barely known species.